Suspicion of Mycosis Fungoides: A Nightmare for Dermatologists and Pathologists - Çalım-Gürbüz, Begüm; Çaytemel, Ceyda; Kuşku-Çabuk, Fatmagül (Cerrahpaşa Medical Journal, 2024)
Objective: Diagnosing mycosis fungoides (MF) poses a challenge both clinically and pathologically. In its early stages, MF may exhibit minimal changes, leading to potential misdiagnosis as benign inflammatory dermatoses. This study aimed to evaluate the clinicopathological features of cases where there is clinical suspicion of MF. Methods: A total of 254 consecutive patients with suspected MF were included in the study. Clinical findings and pathology reports were retrospectively obtained from hospital records, and the clinicopathological features were subjected to statistical analysis. Results: The median age of the study participants was 39.4 ± 19.2 years old (range: 0-85), with 52% being male. Clinical erythematous lesions were significantly more common among participants whose MF had been identified as the initial diagnosis based on clinical preliminary diagnoses (P = .02). Histomorphological MF diagnosis was statistically significant in clinically erythematous lesions, while histomorphological suspicion for MF group was more common in the clinical “other” group (P = .001, P = .03). Hyperchromasia, cytoplasmic halo, and atypical intraepidermal collections of lymphocytes were statistically more prevalent in histomorphological MF diagnoses (P < .001). Conclusion: Although the clinicopathological spectrum of MF diagnosis may vary across disease stages, our study demonstrates the importance of both clinical and pathological examination of erythematous lesions for MF. Compared to other pathological criteria for MF, changes in lymphocyte size and shape may have less significance in determining MF’s pathological suspicion. The best approach for diagnosing MF is to collate accurate data to avoid misdiagnosis. Cite this article as: Çalım-Gürbüz B, Çaytemel C, Kuşku-Çabuk F. Suspicion of mycosis fungoides: A nightmare for dermatologists and pathologists. Cerrahpaşa Med J. 2024;48(1):34-39.